Effect of continuous sub-culturing on infectivity of Clostridium perfringens ATCC13124 in mouse gas gangrene model - Kumar, Ravi Bhushan; Alam, Syed Imteyaz (Folia microbiologica, 2017)
Clostridium perfringens is a Validated Biological Agent and a pathogen of medical, veterinary, and military significance. Gas gangrene is the most destructive of all the clostridial diseases and is caused by C. perfringens type A strains wherein the infection spreads quickly (several inches per hour) with production of gas. Influence of repeated in vitro cultivation on the infectivity of C. perfringens was investigated by comparing the surface proteins of laboratory strain and repository strains of the bacterium using 2DE-MS approach. In order to optimize host-pathogen interaction during experimental gas gangrene infection, we also explored the role of particulate matrix on ability of C. perfringens to cause gas gangrene.
Keywords: zvířata; gangréna plynatá; myši inbrední BALB C; Animals; Disease Models, Animal; Mice, Inbred BALB C; interakce hostitele a patogenu; Bacterial Proteins; Humans; Mice; Gas Gangrene; Clostridium perfringens; myši; Host-Pathogen Interactions; modely nemocí na zvířatech; bakteriální proteiny; lidé